Assessing land suitability for dragon fruit cultivation in Bangladesh: a GIS-based AHP approach - Md. Biplob Hosen; Md. Rabiul Islam; Umme. Tahera-Tun-Humayra; Rifat Sharker; Zarjes Kader; Md. Tareq Aziz; Manik Miah; Mahmudul Hasan; Rokshana Pervin; Md. Amzad Hossain; Md. Tofiquzzaman (Smart Agricultural Technology)
Context: Land Suitability Assessment plays a pivotal role in optimizing agricultural yield and quality, minimizing economic losses, fostering sustainable cultivation practices, and mitigating risks associated with crop production, including that of dragon fruit. Objective: The primary objective of this study was to identify and map suitable lands for dragon fruit cultivation in Bangladesh. Methods: A Multi-Criteria Decision Analysis (MCDA)framework was applied, integrating Geographic Information Systems (GIS) and the Analytical Hierarchy Process (AHP). Ten key parameters representing terrain, climatic, and soil characteristics—temperature, pH, soil organic carbon, salinity, moisture, soil texture, slope, elevation, nutrients, and precipitation—were selected as influential factors. These were weighted using the AHP method, and a weighted overlay analysis was performed within the GIS environment to classify land suitability. Results and conclusions: The analysis revealed that 19,982.93 km² (33.83 %) of the total cultivable land was highly suitable for dragon fruit cultivation. Additionally, 24.64 % was classified as high suitability, followed by 19.22 % as moderate, 19.88 % as low, and 2.43 % as very low suitability. The northwestern region of Bangladesh was identified as the most favorable area for dragon fruit cultivation. These findings underscore the effectiveness of integrating GIS and AHP in land suitability analysis. Significance: This study highlights the potential of GIS-based AHP as a reliable decision-support tool for agricultural land-use planning and policymaking, particularly for introducing and expanding non-traditional crops like dragon fruit in suitable regions.